Mental health, coping strategies, and help-seeking behaviour during the ongoing war in Ukraine: a cross-sectional study - Aneta Bednářová; Yana Kalymon; Pavol Mikula; Nataša Hlaváčová; Ingrid Obsuth; Dominika Jarčušková (International Journal of Public Health, 2026)
Objectives The war in Ukraine has had an impact on the population’s mental health. Displacement, economic instability, loss of loved ones, and shortages of basic resources have contributed to distress, including anxiety, depression, and post-traumatic stress disorder (PTSD). Methods This study examined mental health symptoms and coping strategies in a sample of 100 Ukrainian adults (mean age = 35.5 ± 12.5; 73% female). Participants completed self-report questionnaires assessing symptoms of depression, anxiety, and PTSD, along with stressors, coping, and help-seeking behaviour. Logistic regression was used to identify predictors of mental health outcomes and service use. Results Symptoms of depression were reported by 70% of participants, anxiety by 80%, and 31% met criteria for probable PTSD. Despite this, only 15% sought psychological help. Women were more likely than men to report anxiety and PTSD. Perceived stress significantly predicted mental health outcomes and was associated with a greater likelihood of help-seeking. Conclusion These findings highlight the urgent need to improve access to psychological and psychiatric care in Ukraine.